Focal Times and Spaces: How Ethnography Foregrounds the Spatiotemporality of International Organizations and Global Governance - Julian Eckl (Global Policy, 2022)
Drawing on a long-term political ethnography of sites of global health governance, the paper makes methodological and substantive contributions. First of all, it shows that ethnography induces researchers to experience international organizations (IOs) and global governance as spatiotemporal phenomena. This experience overlaps with the lived realities of practitioners and spotlights aspects that are otherwise easily overlooked. Both practitioners and ethnographers have to be in specific spaces at particular times. This practical challenge illustrates that there are focal times and spaces, which are linked to the cyclical and sited character of global health governance. These focal times and spaces provide an important coordination mechanism and ease the general flow of knowledge – within IOs and between IOs and their environment. However, there is also the constant danger that they develop a self-referential life of their own and become disconnected from other processes. Similarly, not just researchers but also practitioners are struggling to develop a comprehensive understanding of IOs since they experience them only partially and in specific settings. Thus, a spatiotemporal account highlights both overlooked links and unexpected disconnections. The conclusion mentions that the current – COVID-19-induced – mainstreaming of digital technologies will impact the spatiotemporal dimension of global health governance.
Keywords: 320